Basic education in Islamic schools in Indonesia bridging the gab-vision 2025 (Pendidikan dasar sekolah Islam di Indonesia menjembatani celah-visi 2025) : Proceedings regional symposium - Basic... (LAPIS, 2009)
tr, c.1-3